ARRT Development for the Upcoming Human Exploration Missions - S. Hu; S. Monadjemi; J. E. Barzilla; E. Semones (Space Weather)
Abstract The health risks of space radiation present big challenges to space exploration, with the possibility of large Energetic Solar Particle Events (ESPEs) inducing Acute Radiation Sickness (ARS) during upcoming Artemis missions. An operational software Acute Radiation Risks Tool (ARRT) was developed to directly use measurements from onboard dosimeters to project organ doses during times of increased radiation exposure, so that any possible ARS risks of the astronauts can be modeled and monitored in real time using a data stream at the astronaut location. To enable ARRT to handle variant scenarios of any possible ESPEs in an automatic manner for mission operation, two data sets were employed in developing its modules, one involving historical solar protons recorded over the past four decades and the other using the real‐time telemetry readings of dosimeters onboard International Space Station (ISS). Though vastly different in terms of data cadence, smoothness, and data gaps, all events in these data sets can be correctly processed to output organ doses and ARS risks and generate flight notes for communication within the Flight Control Team (FCT). All these tasks are completed with close interactions between multiple modules developed with many state‐of‐the‐art facilities of full stack web applications. This work demonstrates that ARRT meets the requirement to project radiation exposure and to provide clinical guidelines in very short time steps as the ESPE unfolds, even for the longest event in data sets, making this tool eligible to be tested during the upcoming unmanned Artemis mission and utilized in future space exploration.